Ethnomedicine, antibacterial activity, antioxidant potential and phytochemical screening of selected medicinal plants in Dibatie district, Metekel zone, western Ethiopia - Baressa Anbessa; Ermias Lulekal; Ariaya Hymete; Asfaw Debella; Eyob Debebe; Abiy Abebe; Sileshi Degu (BMC, 2024)
Abstract Background Medicinal plants play a major role in the delivery of healthcare, particularly among the rural population of Ethiopia. Plant extracts and their bioactive compounds have been utilized for the treatment of several diseases. This study was aimed at evaluating the antibacterial activity, antioxidant capacity, and phytochemical content of selected medicinal plants used in Dibatie district, western Ethiopia. Methods Study plants were collected, shade dried, pulverized, extracted by maceration in 80% ethanol, and subjected to antibacterial, antioxidant, and phytochemical tests. Minimum inhibitory concentration (MIC) was determined using 96-well microplates and nutrient broth microdilution. Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Phytochemical screening was conducted using standard test methods. Results The ethanolic extract of Polystachya steudneri Rchb.f. pseudobulbs was the most active against gram-negative Proteus mirabilis, Salmonella typhimurium, Klebsiella pneumoniae, Escherichia coli, and Shigella flexneri, with MIC values of 8 ± 0, 11 ± 5, 3 ± 1, 3 ± 1, and 2 ± 0 mg/mL, respectively. The ethanolic extract of P. steudneri was also the most effective against gram-positive Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus agalactiae, and Enterococcus faecalis, with MIC values of 8 ± 0, 8 ± 0, 3 ± 1, and 16 ± 0 mg/mL, respectively. Ethanolic extracts of Gnidia involucrata Steud. ex A.Rich. stems and roots were effective antioxidants, with respective 50% DPPH free radical inhibitory concentrations (IC50) of 168.68 and 181.79 µg/mL, followed by that of P. steudneri (IC50 = 203.11 µg/mL). The study plants contained alkaloids, anthocyanins, anthraquinones, cardiac glycosides, coumarins, flavonoids, phenols, saponins, steroids, tannins, and terpenoids. Conclusions This study confirmed the antibiotic, antioxidant, and phytochemical constituents of the investigated plants and suggested further investigations that may lead to bioactive lead compounds.